P81 Use of systemic antibiotics in Austrian children and adolescents: a survey. Issue 6 (17th May 2019) - Rauch, E; Lagler, FB; Herkner, H; Strenger, V; Male, C
Abstract : Background: Several surveys that have assessed the use of antibiotic medicines for children and adolescents demonstrate significant heterogeneity in prescription patterns between different countries. The liberal use of antibacterial treatment, particularly unjustified use of broad spectrum antibiotics, is one of the main reasons for increasing rates of antibiotic resistance. We have studied antibiotics prescription frequencies in children and adolescents in Austria covering both primary and hospital care settings, in order to obtain a representative survey for our country. Methods: Prescription data for systemic antibiotics were assessed for the year 2014. For primary care, reimbursement data were obtained from Austrian health insurances. For hospital care, information on medicines dispensed to paediatric wards was obtained from hospital pharmacies. Frequencies of systemic antibiotic use were analyzed by Anatomical Therapeutic Chemical classification system, age groups, care setting, and in relation to all other medicines used. Systemic antibiotics were divided into subgroups, like broad and narrow spectrum penicillins, cephalosporins, tetracyclins, and others. Results: Systemic antibiotics comprised 24% and 21% of all medicines prescribed to children and adolescents in primary care and hospital care, respectively. The most frequent were broad spectrum antibiotics (32% and 35% of systemic antibiotics prescribed) in both primary and hospital care settings. Macrolides and 2nd generation cephalosporins were more frequently prescribed in primary care setting, whereas ß-lactam antibiotics other than cephalosporins and antibiotics, such as fluorochinolones, aminoglycosides, or linezolid were more frequently used in hospital. Conclusions: This is the first representative survey investigating the use of systemic antibiotics in children and adolescents in Austria. The study allows comparison of prescription patterns to other European countries: it reveals rather big differences to systemic antibiotics prescription in Italy, the Netherlands and Denmark, whereas prescription patterns are similar in Germany and Austria. Furthermore, this survey provides the basis to assess temporal trends in the future. Disclosure(s): Nothing to disclose